2021
DOI: 10.1371/journal.pntd.0010036
|View full text |Cite
|
Sign up to set email alerts
|

Free-ranging pigs identified as a multi-reservoir of Trypanosoma brucei and Trypanosoma congolense in the Vavoua area, a historical sleeping sickness focus of Côte d’Ivoire

Abstract: Background The existence of an animal reservoir of Trypanosoma brucei gambiense (T. b. gambiense), the agent of human African trypanosomiasis (HAT), may compromise the interruption of transmission targeted by World Health Organization. The aim of this study was to investigate the presence of trypanosomes in pigs and people in the Vavoua HAT historical focus where cases were still diagnosed in the early 2010’s. Methods For the human survey, we used the CATT, mini-anion exchange centrifugation technique and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 60 publications
(104 reference statements)
0
22
0
Order By: Relevance
“…Thanks to its performance in terms of specificity and sensitivity described in humans, TL has become the reference immunological diagnostic tool for the surveillance of g-HAT [3,7,23]. However, its reliability as a diagnostic tool of T. b. gambiense infection in animals has been questioned and further experimental studies proposed to confirm or reject the T. b. gambiense specificity of this method [39]. This was the main objective of this experimental infection conducted in pigs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thanks to its performance in terms of specificity and sensitivity described in humans, TL has become the reference immunological diagnostic tool for the surveillance of g-HAT [3,7,23]. However, its reliability as a diagnostic tool of T. b. gambiense infection in animals has been questioned and further experimental studies proposed to confirm or reject the T. b. gambiense specificity of this method [39]. This was the main objective of this experimental infection conducted in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The immune trypanolysis (TL) based on the detection of antibodies against predominant or specific variant antigen types (VAT) [41] is increasingly used for the epidemiological surveillance of g-HAT [7,8,21,23] and it was also recently applied to animal surveys conducted in Côte d'Ivoire. With positivity rates of up to 50% that were inconsistent with HAT prevalence in the studied hypo-endemic or historical foci, the T. b. gambiense specificity of VAT LiTat 1.3 and LiTat 1.5 was questioned [30,39]. This specificity was also questioned with positive TL results observed with these two VAT in cattle in a rhodesiense HAT and AAT endemic region in Uganda [27].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…An additional difficulty can appear in a “One Health” context: it may be necessary to treat animals infected by zoonotic trypanosomes, not because they are sick, but because they may be a threat to humans as a reservoir. This latter question is increasingly relevant in the context of eliminating transmission of T. b. gambiense (HAT) [ 94 ]. Finally, the treatment’s fully curative effect should be demonstrated in such a context.…”
Section: Diagnostic Tools Available and Needed In Line With Various E...mentioning
confidence: 99%
“…For, instance, it has been recently demonstrated that the emergence of animal reservoirs of Dracunculus medinensis , particularly in fish-consuming domestic dogs (93% of all Guinea worms detected worldwide in 2020 were in dogs in Chad), has become the major impediment to eradication of this human disease 3 4. For human African trypanosomiasis, the importance of latent infections in seropositive asymptomatic individuals,5 the identification of domestic pigs as reservoirs of Trypanosoma brucei gambiense 6 and the probable role of skin-dwelling trypanosomes in transmission maintenance7 8 are active research areas that may be crucial for reaching the elimination goal 9. Actually, the lack of fundamental scientific knowledge about the natural reservoirs and even the transmission of Mycobacterium ulcerans, that still remain elusive in most endemic areas,10 is also pointing to the crucial need for more fundamental knowledge on NTDs.…”
Section: Impact Of Multidisciplinary Fundamental Research On Ntd Controlmentioning
confidence: 99%